Modeling and simulation of multivariable liquid process rig - 462666 Fareg Mohamed Aldebrez; Mir Hasib Azam; Mortaza Mohamed, 1957-; International Conference on Robotics, Vision and Parallel Processing for Industrial Automation (1996 : USM, Perak)
22